Supplemental feeding solutions do not improve honey bee (Hymenoptera: Apidae) foraging on cranberry (Vaccinium macrocarpon). Issue 5 (19th October 2020) - Lois, Abby N.; Jaffe, Benjamin; Guédot, Christelle
Abstract : Most cranberry ( Vaccinium macrocarpon ) growers rent honey bees ( Apis spp .) to insure proper pollination of their crop. However, honey bees are not the most efficient pollinators of cranberry and there have been increasing efforts to improve the pollination services provided by honey bees. Cranberry flowers provide small amounts of nectar and this research project tested whether supplementing hives with various sugar sources could increase the amount of cranberry pollen foraged. High fructose corn syrup, honey, and sucrose did not increase the amount of cranberry pollen, or the percent of cranberry pollen, foraged and returned to the hive. However, overall weights of the pollen samples were significantly higher for hives treated with high fructose corn syrup and sucrose compared to hives supplied with honey, water, or no additional solutions. Although not explicitly tested in this study, these results suggest that honey bees are incorporating these carbohydrates into their pollen bundles. However, since the supplemental sugar feedings did not increase the amount, or percentage, of cranberry pollen grains foraged, there is limited evidence that supplemental sugar feedings will improve honey bee pollination services in cranberry. Future work in this area should examine the relationships between pollen quality and supplemental sugar feedings, as these feeding may improve hive health in crops with poorer quality floral resources.